Daily changes of salivary secretory immunoglobulin A and appearance of upper respiratory symptoms during physical training - Nakamura, C.; Akimoto, T.; Suzuki, S.; Kono, I. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: It is well known that highly trained athletes suffer from a high incidence of upper respiratory tract infections (URTI). Secretory immunoglobulin A (SIgA) is a major effector of mucosal surface protection against microorganisms causing URTI. Although several studies have investigated the relationship between falls in SIgA levels and appearance of URTI symptoms, the relationship is not yet clear. Methods: We prospectively investigated the relationship between daily changes in SIgA and appearance of URTI symptoms in collegiate soccer players during a training period of 2 months. Results: Five of 12 subjects exhibited URTI symptoms during the study period. The SIgA level did not significantly decrease before appearance of URTI symptoms. However, the saliva flow rate and SIgA secretion rate tended to decrease 3 days before the appearance of URTI symptoms compared to that in the non-infection period (31.3±19, -42.2±20.6%, respectively). Conclusion: We could not demonstrate a significant relationship between decreased SIgA levels and appearance of URTI symptoms during the training period. However, our findings suggest that monitoring of SIgA secretion rate may be useful for assessment of risk status of athletes for URTI.